2009
DOI: 10.1136/ard.2009.118158
|View full text |Cite
|
Sign up to set email alerts
|

Levels of plasmacytoid dendritic cells and type-2 myeloid dendritic cells are reduced in peripheral blood of patients with primary Sjögren's syndrome

Abstract: Patients with pSS have alterations among DC populations in PB, and pDC are present in the SG, suggesting a potential role of these cells in SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
9
40
0
3
Order By: Relevance
“…A greater number of IFNa-producing PDCs compared to control tissues were detected in pSS MSG biopsies [14,24]. PDCs as well as the mDC2 subset of myeloid dendritic cells have been shown to be reduced in the peripheral blood from these patients compared to controls, implying their influx into MSG target tissues [25]. A similar situation is described in a wide array of autoimmune disorders.…”
Section: Ifna Producing Cells In Pssmentioning
confidence: 82%
“…A greater number of IFNa-producing PDCs compared to control tissues were detected in pSS MSG biopsies [14,24]. PDCs as well as the mDC2 subset of myeloid dendritic cells have been shown to be reduced in the peripheral blood from these patients compared to controls, implying their influx into MSG target tissues [25]. A similar situation is described in a wide array of autoimmune disorders.…”
Section: Ifna Producing Cells In Pssmentioning
confidence: 82%
“…The locally increased IFN signature has later been confirmed along with the presence of pDC in the salivary glands by direct staining with CD123 and BDCA-2 pDC markers [44]. Besides the occurrence of pDC in the inflammatory foci, reduced levels of pDC were found in peripheral blood from patients with Sjögren's syndrome [45,46], suggesting the recruitment of pDC to the target organ, but a direct connection still needs to be established. The increased IFN signature in patients with Sjögren's syndrome seems not to be only locally restricted to the salivary glands, as a recent study identified an increased expression of IFN inducible genes also in monocytes from Sjögren's syndrome patients [45].…”
Section: Dendritic Cells In Sjögren's Syndromementioning
confidence: 89%
“…CD83 is expressed only on activated DC, whereas CD1a is predominately known as a marker for Langerhans cells, a certain type of dermal DC, as well as monocyte-derived DC. Decreased levels of the CD141 + mDC2 subset were found in peripheral blood from patients with Sjögren's syndrome [46]. Nevertheless, it still needs to be proven whether mDC2 are actually present in the salivary glands of these patients.…”
Section: Dendritic Cells In Sjögren's Syndromementioning
confidence: 98%
“…Serum levels of IFNa were increased in only some pSS patients and IFNa-mRNA levels were only slightly elevated in peripheral blood cells compared to controls [11,12]. Plasmacytoid dendritic cells (pDCs) are main producers of IFNa and these cells were demonstrated in the salivary glands of pSS patients, but not in controls [13,14]. Since reduced levels of pDCs were found in peripheral blood from patients with pSS, the findings suggest that pDCs are recruited into the salivary glands and are involved in disease pathogenesis [14].…”
Section: Role Of Type I Interferon (Ifna/b)mentioning
confidence: 99%
“…Plasmacytoid dendritic cells (pDCs) are main producers of IFNa and these cells were demonstrated in the salivary glands of pSS patients, but not in controls [13,14]. Since reduced levels of pDCs were found in peripheral blood from patients with pSS, the findings suggest that pDCs are recruited into the salivary glands and are involved in disease pathogenesis [14]. Whether these cells are the major source of type I IFN in pSS patients is, however, not known and ductal epithelial cells likely contribute to (circulating) type I IFN levels [15].…”
Section: Role Of Type I Interferon (Ifna/b)mentioning
confidence: 99%